2023
DOI: 10.26668/businessreview/2023.v8i2.1146
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Leadership, Discipline, Satisfaction, and Performance: A Case Study of Steel Manufacture in Indonesia

Abstract: Purpose: The aim of this study is to predict the relationship of leadership, discipline, satisfaction, and performance.   Theoretical framework: The framework was developed based on the relationship of transactional leadership, transformational leadership, work discipline, job satisfaction, and employee performance.   Design/methodology/approach: The study use quantitative approach. Data were collected by distributing questionnaires to 100 respondents. Data were analyzed statistically use smartPLS.   Findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…The leadership is also seen to be connected with some other cadet members; in other words, the leadership does not only want to talk and discuss with certain people so that there is no clustering among cadet members. This is in accordance with the findings of Suranata et al (2022), who found that autocratic leadership style has a positive and significant effect on work discipline at the Bali Province Language Center, as well as the findings of Suhartono et al (2023), who found that leadership style has an effect on employee work discipline at the Tasikmalaya education office.…”
Section: Discussion Leadership Style On Cadet's Attitudessupporting
confidence: 92%
“…The leadership is also seen to be connected with some other cadet members; in other words, the leadership does not only want to talk and discuss with certain people so that there is no clustering among cadet members. This is in accordance with the findings of Suranata et al (2022), who found that autocratic leadership style has a positive and significant effect on work discipline at the Bali Province Language Center, as well as the findings of Suhartono et al (2023), who found that leadership style has an effect on employee work discipline at the Tasikmalaya education office.…”
Section: Discussion Leadership Style On Cadet's Attitudessupporting
confidence: 92%
“…This can be seen from employees who attend and leave on time according to working hours or operational hours set by KCU Surabaya 60000. Discipline is an important thing because as in (Suhartono et al, 2023) it is explained that discipline is a very essential or basic thing. so that every activity can run smoothly, without discipline it will not be successful.…”
Section: Fund Distribution and Bank Channelingmentioning
confidence: 99%
“…Agood impression is job satisfaction regarding the results of work based on an assessment of its qualities. (Suhartono et al, 2023).…”
Section: Employee Satisfaction 1)mentioning
confidence: 99%